-(-9x-9y+4)=

Simple and best practice solution for -(-9x-9y+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-9x-9y+4)= equation:


Simplifying
-1(-9x + -9y + 4) = 0

Reorder the terms:
-1(4 + -9x + -9y) = 0
(4 * -1 + -9x * -1 + -9y * -1) = 0
(-4 + 9x + 9y) = 0

Solving
-4 + 9x + 9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 9x + 4 + 9y = 0 + 4

Reorder the terms:
-4 + 4 + 9x + 9y = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 9x + 9y = 0 + 4
9x + 9y = 0 + 4

Combine like terms: 0 + 4 = 4
9x + 9y = 4

Add '-9y' to each side of the equation.
9x + 9y + -9y = 4 + -9y

Combine like terms: 9y + -9y = 0
9x + 0 = 4 + -9y
9x = 4 + -9y

Divide each side by '9'.
x = 0.4444444444 + -1y

Simplifying
x = 0.4444444444 + -1y

See similar equations:

| 3.5x=21 | | 4y^2-25x^2=100 | | 144=16t^2 | | 5=p+3 | | .3x+1.8=8 | | 3a-8a= | | 15x-2y=10 | | 5-.5x-3=4 | | 43y=6(7y-2) | | 6y=5(y+3) | | (x-3)(2x+3)=0 | | 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 | | 2x^2+25=25 | | 2x^2-25=25 | | 2z^2+5=167 | | 15x+3y=12 | | 2x+5x+34*6/46=8 | | 2x+5xx=990 | | x^2=11 | | 2x+5-(2573)-257xxx=2 | | 2x+x^2=12 | | 2x+5-(-4)=4x | | 7-10x^2=1 | | 2x+72=0 | | 7x+7(x-60)=5180 | | x+(-12)=4 | | .5x+6=.3x | | .5+6=.3x |

Equations solver categories